Learning by doing, organizational forgetting, and the business cycle - Bongers-Chicano, Aneli María (Wiley, 2022)
This paper supplements a learning-by-doing real busi-ness cycle model with endogenous organizational for-getting. Empirical evidence shows that the accumulatedexperience decay rate is not constant over the busi-ness cycle, but that forgetting is a function of economicactivity. Learning reinforces the effects of productivityshocks, and organizational forgetting exacerbates theirimpact and increases their persistence. This is of partic-ular interest when a negative productivity shock hits theeconomy,astheincreasingspeedofforgettingaggravatesthe negative shock and delays recovery.
Keywords: Ciclos económicos; Business cycle; Learning by doing; Organizational forgetting